Super-thick silver-containing chromium nitride coating and preparation method thereof

Through magnetron sputtering-cathode arc combined coating technology, silver-containing chromium nitride coating with a thickness of 30 to 80 μm was deposited on the substrate, which solved the problem of large thickness, low friction coefficient, wear resistance and uniform composition and tissue in the prior art. The problem of the development of plating has achieved self-lubricating friction reduction performance in high temperature environments, significantly improving the performance and life of the piston assembly.

CN119392166APending Publication Date: 2025-02-07FUJIAN UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411516244.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The prior art is difficult to develop plating with high thickness, low coefficient of friction, wear resistance and composition and tissue uniformity, especially in high temperature environments, with insufficient self-lubricating thick coatings for piston rings.

Method used

The magnetron sputtering-cathode arc combined coating method is used to deposit silver chromium nitride coating with a thickness of 30 to 80 μm on the substrate. By controlling the power supply power of the magnetron sputtering silver target and the cathode arc chromium target, the coating composition is ensured. The silver/chromium atom content ratio in the content is 0.05 to 0.2.

Benefits of technology

A coating with self-lubricating friction reduction performance in an environment of 380~500℃ has been achieved, which significantly improves the friction reduction, wear resistance and service life of the piston assembly. At the same time, it solves the insufficient thickness of conventional magnetron sputtering coating and cathode arc deposition content. Problems of quality defects in low melting point metal coatings.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119392166A_ABST
    Figure CN119392166A_ABST
Patent Text Reader

Abstract

The invention discloses an ultra-thick silver-containing chromium nitride coating and a preparation method thereof, and belongs to the field of metal material surface protection. The plating layer is a uniform single-layer silver-containing chromium nitride plating layer deposited on a substrate by adopting a magnetron sputtering-cathode arc combined coating method, the thickness of the silver-containing chromium nitride plating layer is 30-80 microns, and the structure of the silver-containing chromium nitride plating layer is formed by compounding nanocrystalline silver and nanocrystalline chromium nitride. According to the invention, the problems of insufficient thickness of a conventional magnetron sputtering coating and quality defect during cathode arc deposition of the coating containing low-melting-point metal are simultaneously solved, the coating is suitable for a metal workpiece taking a piston ring as a main application object, and the antifriction and wear-resisting properties of a high-power-density engine under high-temperature harsh lubrication conditions can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of metal material surface protection, and in particular to an ultra-thick silver-containing chromium nitride coating and a preparation method thereof. Background Art

[0002] The surface of mechanical parts such as piston rings requires a thick coating to meet the requirements of long life and wear resistance. The cathode arc evaporation coating has high deposition efficiency and large thickness, and is the mainstream technology for coating the piston ring surface with a thickness of more than 10μm. The combustion chamber temperature of the new high-power density engine is high, the linear speed of the piston movement is accelerated, and the lubrication efficiency of the piston auxiliary lubricant is significantly reduced. Therefore, extremely high friction reduction and wear resistance performance requirements are put forward for the piston ring surface coating, and there is currently no reliable self-lubricating thick coating.

[0003] Soft metals are good high-temperature lubricating materials. AlSn series coatings are often used for anti-friction protection of bearing surfaces. However, the anti-friction coating for piston rings must also have wear resistance, and has high requirements for the coating composition and structure. The Chinese patent "Titanium-aluminum-silver-nitrogen nanocomposite coating and its preparation method (2012105503968)", the literature "High-Temperature Tribological Behavior of CrN-Ag Self-lubricating Coatings (2006), Microstructure and tribological performance of adaptive MoN-Ag nanocomposite coatings with various Ag contents (2022)" and others all report that silver nitride films prepared by magnetron sputtering have self-lubricating properties at medium and high temperatures, and their effective anti-friction and wear-resistant temperature is consistent with the service environment of piston rings for high power density engines. However, due to the limitation of magnetron sputtering coating deposition efficiency, magnetron sputtering coatings are all less than 10μm, which cannot meet the thickness requirements for long-term service of piston rings.

[0004] From the perspective of coating development, a silver-containing anti-friction and wear-resistant thick coating is prepared, which consists of two types: nano-multilayer and nano-composite of "silver / hard phase". Among them, the nano-multilayer coating is formed by alternating deposition of silver monolayer and hard phase monolayer. At present, "Ti / TiN" and "Cr / CrN" nano-multilayer coatings with a thickness of 10 to 30 μm have been developed using cathode arc evaporation technology for surface protection of tools and molds. Although the nano-multilayer structure coating has the advantages of low stress and large deposition thickness, the coating is constantly worn during use, resulting in uneven changes in the composition, friction coefficient and wear rate of the friction surface, which in turn affects the performance stability of special friction components and is not suitable for piston ring coatings.

[0005] The "silver / hard phase" nanocomposite structure coating with uniform composition along the thickness direction is an ideal coating scheme. It is assumed that in the "silver / hard phase" nanocomposite structure coating, the appropriate amount of silver and hard phase are evenly distributed in the form of two crystalline phases of micro-nano particles. At working temperature, silver acts as a self-lubricant, while the hard phase plays a supporting and anti-wear role. However, the development of thick coatings of the "silver / hard phase" nanocomposite structure by cathode arc evaporation is difficult. This is because silver has a low melting point and a high saturated vapor pressure. When it is co-evaporated with the components that constitute the hard phase, the silver droplets splash violently, and the coating has poor composition uniformity, resulting in poor quality stability of the coating under working conditions. Therefore, developing a coating with large thickness, low friction coefficient, wear resistance, and good composition and organizational uniformity is an important problem in this field. Summary of the invention

[0006] The object of the present invention is to provide an ultra-thick silver-containing chromium nitride coating and a preparation method thereof.

[0007] In order to achieve the above object, the present invention adopts the following technical solution:

[0008] The invention discloses an ultra-thick silver-containing chromium nitride coating, which is a uniform single-layer silver-containing chromium nitride coating deposited on a substrate by a magnetron sputtering-cathode arc combined coating method. The structure of the silver-containing chromium nitride coating is composed of nanocrystalline silver and nanocrystalline chromium nitride. The thickness of the silver-containing chromium nitride coating is 30 to 80 μm, and the composition of the silver-containing chromium nitride coating is 0.05 to 0.2 in terms of the silver / chromium atomic content ratio.

[0009] The ultra-thick silver-containing chromium nitride coating is prepared by using a magnetron sputtering-cathode arc combined coating apparatus, the center of the coating chamber of the coating apparatus is a rotatable workpiece holder for placing the substrate, and 9 cathode arc chromium targets and 9 magnetron sputtering silver targets are arranged in sequence on the inner wall of the chamber. The target positions of the above 18 targets are distributed according to the inner wall of the chamber: the cathode arc chromium targets and the magnetron sputtering silver targets are arranged in three rows and six columns, and the cathode arc chromium targets and the magnetron sputtering silver targets are distributed at intervals in the horizontal and vertical directions, and then the coating is performed according to the following steps:

[0010] (1) Clamping the cleaned and dried substrate on a rotatable workpiece holder and sending it into the coating chamber of a magnetron sputtering-cathode arc combined coating apparatus;

[0011] (2) Evacuate the coating chamber to a vacuum level below 2×10 -3 Pa, control the rotation speed of the turret and the substrate to 2-12 rpm, heat the substrate to 300-430°C and maintain the temperature, and introduce argon gas with a flow rate of 500 sccm;

[0012] (3) Set the bias voltage to -800 V, start all cathode arc chromium targets and keep the cathode arc chromium target current at 30 A, start all magnetron sputtering silver targets and keep the magnetron sputtering silver target current at 0.2 A, and maintain for 5 to 15 minutes to clean the target material and substrate;

[0013] (4) The bias voltage is adjusted to -20 to -100 V. At the same time, the current of the cathode arc chromium target is increased to 120 A, and the current of the magnetron sputtering silver target is increased to 0.5 to 3 A. A nitrogen flow rate of 250 sccm is introduced and maintained. All cathode arc chromium targets and all magnetron sputtering silver targets are kept working simultaneously for 6 to 15 hours to plate a silver-containing chromium nitride coating on the substrate.

[0014] Preferably, the chamber temperature during the coating process is 380-400° C., and the negative bias voltage of the substrate during the deposition of the silver-containing chromium nitride coating is -40V.

[0015] Furthermore, the substrate is an iron-based alloy, and the iron-based alloy is subjected to surface strengthening treatment, and the surface strengthening treatment method is nitriding or pre-plating of chromium plating.

[0016] The present invention adopts magnetron sputtering-cathode arc combined deposition technology to form a silver-containing chromium nitride coating with a thickness of 30 to 80 μm on a substrate. The silver is deposited by magnetron sputtering silver target, and the chromium nitride is obtained by cathode arc evaporation of the chromium target in a nitrogen-containing atmosphere. The arrangement and layout of the magnetron sputtering target (pure silver) and the cathode arc evaporation target (pure chromium) adopted in the present invention is a necessary condition for forming a uniform single-layer coating with a composite structure of nanocrystalline silver and nanocrystalline chromium nitride.

[0017] The present invention has the following beneficial effects:

[0018] 1. The present invention controls the power of the magnetron sputtering silver target and the cathode arc evaporation chromium target, so that the silver / chromium atomic content ratio in the coating composition is 0.05-0.2, and has good bonding strength and hardness.

[0019] 2. The silver-containing chromium nitride coating of the present invention has self-lubricating and friction-reducing properties when in contact and friction with alloys, ceramics and other materials at 380-500°C. The ultra-thick silver-containing chromium nitride coating of the present invention is particularly suitable for coating of piston ring components of high-power density engines, and improves the friction reduction, wear resistance and service life of piston components under high-temperature and severe lubrication conditions.

[0020] 3. The present invention solves the problems of insufficient coating thickness in conventional magnetron sputtering and quality defects in cathode arc deposition of coatings containing low melting point metals. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 It is a schematic diagram of the coating of the present invention.

[0022] Figure 2 The figure is a top view of the chamber of the magnetron sputtering-cathode arc combined coating apparatus of the present invention.

[0023] Figure 3 The invention discloses a magnetron sputtering-cathode arc combined coating apparatus chamber in which the cathode arc target position and the magnetron sputtering target position are distributed as viewed from the side.

[0024] Figure 4 After coating the outer side of a piston ring formed of an iron alloy with a coating using the method of Example 3, a cross section is taken for observation.

[0025] Figure 5 Surface morphology of the coatings deposited on the iron alloy substrate by different processes

[0026] Figure 6 Comparison results of X-ray diffraction patterns of coatings with different implementation processes. DETAILED DESCRIPTION

[0027] The invention discloses an ultra-thick silver-containing chromium nitride coating, wherein the coating is a uniform single-layer silver-containing chromium nitride coating deposited on a substrate by using a magnetron sputtering-cathode arc combined coating technology. The chamber structure is as follows: a rotatable workpiece holder for placing a substrate is located at the center of a coating chamber of a coating apparatus, and nine cathode arc chromium targets and nine magnetron sputtering silver targets are sequentially arranged around the inner wall of the chamber. The target positions of the above 18 targets are distributed as follows according to the inner wall of the chamber: the cathode arc chromium targets and the magnetron sputtering silver targets are arranged in three rows and six columns, and the cathode arc chromium targets and the magnetron sputtering silver targets are spaced in the horizontal and vertical directions (such as Figure 3 The prepared silver-containing chromium nitride coating has a thickness of 30 to 80 μm, a structure of the silver-containing chromium nitride coating composed of nanocrystalline silver and nanocrystalline chromium nitride, and a composition of the silver-containing chromium nitride coating having a silver / chromium atomic content ratio of 0.05 to 0.2.

[0028] The steps of preparing the silver-containing chromium nitride coating using the iron alloy as the matrix are as follows:

[0029] (1) Clamping the cleaned and dried substrate on a rotatable workpiece holder and sending it into the coating chamber of a magnetron sputtering-cathode arc combined coating apparatus;

[0030] (2) Evacuate the coating chamber to a vacuum level below 2×10 -3 Pa, control the rotation speed of the turret and the substrate to 2-12 rpm, heat the substrate to 300-430°C and maintain the temperature, and introduce argon gas with a flow rate of 500 sccm;

[0031] (3) Set the bias voltage to -800 V, start all cathode arc chromium targets and keep the cathode arc chromium target current at 30 A, start all magnetron sputtering silver targets and keep the magnetron sputtering silver target current at 0.2 A, and maintain for 5 to 15 minutes to clean the target material and substrate;

[0032] (4) The bias voltage is adjusted to -20 to -100 V. At the same time, the current of the cathode arc chromium target is increased to 120 A, and the current of the magnetron sputtering silver target is increased to 0.5 to 3 A. A nitrogen flow rate of 250 sccm is introduced and maintained. All cathode arc chromium targets and all magnetron sputtering silver targets are kept working simultaneously for 6 to 15 hours to plate a silver-containing chromium nitride coating on the substrate.

[0033] Example 1

[0034] The ultra-thick silver-containing chromium nitride coating is deposited on the iron alloy substrate by magnetron sputtering-cathode arc combined coating technology. The vacuum chamber structure is as follows: the center of the coating chamber of the coating apparatus is a rotatable workpiece holder for placing the substrate, and 9 cathode arc chromium targets and 9 magnetron sputtering silver targets are arranged in sequence on the inner wall of the chamber. The target positions of the above 18 targets are distributed according to the inner wall of the chamber: the cathode arc chromium targets and magnetron sputtering silver targets are arranged in three rows and six columns, and the cathode arc chromium targets and magnetron sputtering silver targets are distributed at intervals in the horizontal and vertical directions (such as Figure 3 Then follow the steps below to coat the film:

[0035] (1) Clamping the cleaned and dried substrate on a rotatable workpiece holder and sending it into the coating chamber of a magnetron sputtering-cathode arc combined coating apparatus;

[0036] (2) Evacuate the coating chamber to a vacuum level below 2×10 -3 Pa, control the rotation speed of the turret and the substrate to 6 rpm, heat the substrate to 4000°C and maintain the temperature, and introduce argon gas with a flow rate of 500 sccm;

[0037] (3) Set the bias voltage to -800 V, start all cathode arc chromium targets and keep the cathode arc chromium target current at 30 A, start all magnetron sputtering silver targets and keep the magnetron sputtering silver target current at 0.2 A, and maintain for 10 min to clean the target and substrate;

[0038] (4) The bias voltage is adjusted to -40 V. At the same time, the current of all cathode arc chromium targets is increased to 120 A, and the current of all magnetron sputtering silver targets is increased to 0.5 A. A nitrogen flow rate of 250 sccm is introduced and maintained. All cathode arc chromium targets and all magnetron sputtering silver targets are kept working simultaneously for 10 hours to plate a silver-containing chromium nitride coating on the substrate.

[0039] The thickness of the silver-containing chromium nitride coating plated on the iron alloy substrate is 50 μm, the silver / chromium atomic ratio in the coating is 0.05, the Vickers hardness measured with a force of 100 g is 2100±100, and the coating tissue composition is nanocrystalline silver+nanocrystalline chromium nitride, as shown in Table 1.

[0040] Example 2

[0041] The ultra-thick silver-containing chromium nitride coating is deposited on the iron alloy substrate by magnetron sputtering-cathode arc combined coating technology. The vacuum chamber structure is as follows: the center of the coating chamber of the coating apparatus is a rotatable workpiece holder for placing the substrate, and 9 cathode arc chromium targets and 9 magnetron sputtering silver targets are arranged in sequence on the inner wall of the chamber. The target positions of the above 18 targets are distributed according to the inner wall of the chamber: the cathode arc chromium targets and magnetron sputtering silver targets are arranged in three rows and six columns, and the cathode arc chromium targets and magnetron sputtering silver targets are distributed at intervals in the horizontal and vertical directions (such as Figure 3 Then follow the steps below to coat the film:

[0042] (1) Clamping the cleaned and dried substrate on a rotatable workpiece holder and sending it into the coating chamber of a magnetron sputtering-cathode arc combined coating apparatus;

[0043] (2) Evacuate the coating chamber to a vacuum level below 2×10 -3 Pa, control the rotation speed of the turret and the substrate to 6 rpm, heat the substrate to 4000°C and maintain the temperature, and introduce argon gas with a flow rate of 500 sccm;

[0044] (3) Set the bias voltage to -800 V, start all cathode arc chromium targets and keep the cathode arc chromium target current at 30 A, start all magnetron sputtering silver targets and keep the magnetron sputtering silver target current at 0.2 A, and maintain for 10 min to clean the target and substrate;

[0045] (4) The bias voltage is adjusted to -40 V. At the same time, the current of all cathode arc chromium targets is increased to 120 A, and the current of all magnetron sputtering silver targets is increased to 0.5 A. A nitrogen flow rate of 250 sccm is introduced and maintained. All cathode arc chromium targets and all magnetron sputtering silver targets are kept working simultaneously for 10 hours to plate a silver-containing chromium nitride coating on the substrate.

[0046] The thickness of the silver-containing chromium nitride coating plated on the cemented carbide substrate is 50 μm, the silver / chromium atomic ratio in the coating is 0.1, the Vickers hardness measured with a force of 100 g is 1900±100, and the coating tissue composition is nanocrystalline silver+nanocrystalline chromium nitride, as shown in Table 1.

[0047] Example 3

[0048] The ultra-thick silver-containing chromium nitride coating is deposited on the iron alloy substrate by magnetron sputtering-cathode arc combined coating technology. The vacuum chamber structure is as follows: the center of the coating chamber of the coating apparatus is a rotatable workpiece holder for placing the substrate, and 9 cathode arc chromium targets and 9 magnetron sputtering silver targets are arranged in sequence on the inner wall of the chamber. The target positions of the above 18 targets are distributed according to the inner wall of the chamber: the cathode arc chromium targets and magnetron sputtering silver targets are arranged in three rows and six columns, and the cathode arc chromium targets and magnetron sputtering silver targets are distributed at intervals in the horizontal and vertical directions (such as Figure 3 Then follow the steps below to coat the film:

[0049] (1) Clamping the cleaned and dried substrate on a rotatable workpiece holder and sending it into the coating chamber of a magnetron sputtering-cathode arc combined coating apparatus;

[0050] (2) Evacuate the coating chamber to a vacuum level below 2×10 -3 Pa, control the rotation speed of the turret and the substrate to 6 rpm, heat the substrate to 360°C and maintain the temperature, and introduce argon gas with a flow rate of 500 sccm;

[0051] (3) Set the bias voltage to -800 V, start all cathode arc chromium targets and keep the cathode arc chromium target current at 30 A, start all magnetron sputtering silver targets and keep the magnetron sputtering silver target current at 0.2 A, and maintain for 10 min to clean the target and substrate;

[0052] (4) The bias voltage is adjusted to -40 V. At the same time, the current of all cathode arc chromium targets is increased to 120 A, and the current of all magnetron sputtering silver targets is increased to 3 A. A nitrogen flow rate of 250 sccm is introduced and maintained. All cathode arc chromium targets and all magnetron sputtering silver targets are kept working simultaneously for 15 hours to plate a silver-containing chromium nitride coating on the substrate.

[0053] The thickness of the silver-containing chromium nitride coating plated on the iron alloy substrate is 80 μm, the silver / chromium atomic ratio in the coating is 0.2, the Vickers hardness measured with a force of 100 g is 1400±120, and the coating tissue composition is nanocrystalline silver+nanocrystalline chromium nitride, as shown in Table 1.

[0054] Comparative Example

[0055] The chromium nitride coating is deposited on the substrate using cathode arc coating technology. The difference between the vacuum chamber structure and that of Example 1 is that 9 magnetron sputtering silver targets ( Figure 3 The steps of preparing the silver-containing chromium nitride coating on the iron alloy substrate are as follows:

[0056] (1) Clamp the cleaned and dried substrate on a workpiece holder and place it into the coating chamber of a cathode arc coating machine;

[0057] (2) The coating chamber is evacuated to 2×10 -3 Pa, control the rotation speed of the turret and substrate to 6 rpm, heat the substrate to 400°C and maintain it, and introduce argon gas with a flow rate of 500 sccm;

[0058] (3) Set the bias voltage to -800 V, start all cathode arc chromium targets and maintain the current at 30 A, and clean the targets and substrates for 10 min;

[0059] (4) Adjust the bias voltage to -40 V, start all cathode arc silver targets and maintain the current at 30 A. At the same time, increase the current of all cathode arc chromium targets to 120 A. At the same time, introduce and maintain the nitrogen flow rate at 250 sccm, and keep all cathode arc targets working simultaneously for 11 hours.

[0060] The thickness of the silver-containing chromium nitride coating plated on the iron alloy substrate is 50 μm, the Vickers hardness measured with a force of 100 g is 1100±300, and the coating structure composition is polycrystalline silver+nanocrystalline chromium nitride, as shown in Table 1.

[0061] Implementation Effect

[0062] Table 1

[0063]

[0064] Figure 4 After the coating was applied to the outer side of the ferroalloy piston ring using the method of Example 3, a cross section was taken for observation. The results showed that the thickness of the silver-containing chromium nitride coating on the ferroalloy substrate was 80 μm, the coating was evenly distributed on the outer end surface of the ferroalloy substrate, and the coating was well bonded to the ferroalloy substrate. Magnification observation showed that the coating structure was dense, there were no large particle defects on the cross section, and there were no obvious particles or other defects on the outer end surface of the coating.

[0065] Figure 5 The surface morphology of the coatings plated on the iron alloy substrate by different implementation processes is shown in the results. The coatings of Example 1 and Example 3 have a small amount of chromium droplets on their surfaces, while the coating of the comparative example has a large amount of silver droplets on its surface.

[0066] Figure 6 The comparison results of X-ray diffraction patterns of coatings with different implementation processes. The results show that compared with Example 1 and Example 2, the comparative example presents obvious Ag (111) texture. The Ag (111) texture indicates that there are more large Ag particles in the coating, which is related to the splashing of silver target droplets caused by the comparative example implementation scheme. Large Ag particles will reduce the hardness and wear resistance of the coating, causing the coating performance to decline. The X-ray diffraction pattern shows that the implementation schemes of Example 1 and Example 2 are better than the comparative example.

[0067] The coating structure composition of Example 1, Example 2 and Example 3 is nanocrystalline silver + nanocrystalline chromium nitride, and the coating structure composition of the comparative example is polycrystalline silver + nanocrystalline chromium nitride. The magnetron sputtering-cathode arc combined deposition technology and process range of the present invention are necessary conditions for achieving the coating structure composition and being deposited into an ultra-thick coating with a thickness of 30 to 80 μm. Figure 2 and Figure 3The magnetron sputtering-cathode arc combined coating apparatus and the distribution of the cathode arc target and the magnetron sputtering target in the side view of its chamber are equipment requirements for achieving a uniform silver-containing chromium nitride single-layer coating. Among them, regulating the current of the magnetron sputtering target (pure silver) at 0.5 to 3A is a key process for achieving a coating composition with a silver / chromium atomic ratio of 0.05 to 0.2. The magnetron sputtering-cathode arc combined coating technology adopted in the present invention takes into account high deposition rate, low droplet splashing, optimized atomic diffusion reaction and crystallization ability, so that the coating with a silver / chromium atomic ratio of 0.05 to 0.2 presents a "nanocrystalline silver + nanocrystalline chromium nitride" tissue composition. As shown in the comparative example of the present invention, when a single cathode arc coating is used in this equipment, it is impossible to obtain the corresponding tissue, thereby affecting the uniformity of its performance.

Claims

1. An ultra-thick silver-containing chromium nitride coating, characterized in that: The coating is a uniform single-layer silver-containing chromium nitride coating deposited on a substrate by a magnetron sputtering-cathode arc combined coating method. The structure of the silver-containing chromium nitride coating is composed of a composite of nanocrystalline silver and nanocrystalline chromium nitride. The thickness of the silver-containing chromium nitride coating is 30 to 80 μm. The silver-containing chromium nitride coating is prepared by a magnetron sputtering-cathode arc combined coating apparatus. The center of the coating chamber of the coating apparatus is a rotatable workpiece holder for placing the substrate. Nine cathode arc chromium targets and nine magnetron sputtering silver targets are arranged in sequence on the inner wall of the chamber. The target positions of the above 18 targets are distributed according to the inner wall of the chamber as follows: the cathode arc chromium targets and the magnetron sputtering silver targets are arranged in three rows and six columns, and the cathode arc chromium targets and the magnetron sputtering silver targets are distributed at intervals in the horizontal and vertical directions.

2. The method for preparing an ultra-thick silver-containing chromium nitride coating according to claim 1, characterized in that: The following steps are involved: (1) Clamping the cleaned and dried substrate on a rotatable workpiece holder and sending it into a coating chamber of a magnetron sputtering-cathode arc combined coating apparatus; (2) Evacuate the coating chamber to a vacuum level below 2×10 -3 Pa, control the rotation speed of the turret and the substrate to 2-12 rpm, heat the substrate to 300-430°C and maintain the temperature, and introduce argon gas with a flow rate of 500 sccm; (3) Set the bias voltage to -800 V, start all cathode arc chromium targets and keep the cathode arc chromium target current at 30 A, start all magnetron sputtering silver targets and keep the magnetron sputtering silver target current at 0.2 A, and maintain for 5 to 15 minutes to clean the target material and substrate; (4) The bias voltage is adjusted to -20 to -100 V. At the same time, the current of the cathode arc chromium target is increased to 120 A, and the current of the magnetron sputtering silver target is increased to 0.5 to 3 A. A nitrogen flow rate of 250 sccm is introduced and maintained. All cathode arc chromium targets and all magnetron sputtering silver targets are kept working simultaneously for 6 to 15 hours to plate a silver-containing chromium nitride coating on the substrate.

3. The method for preparing an ultra-thick silver-containing chromium nitride coating according to claim 2, characterized in that: The composition of the silver-containing chromium nitride plating layer is 0.05-0.2 in terms of the silver / chromium atomic content ratio.

4. The method for preparing an ultra-thick silver-containing chromium nitride coating according to claim 2, characterized in that: The chamber temperature during the coating process is 380-400° C., and the bias voltage of the substrate when depositing the silver-containing chromium nitride coating is -40V.

5. The method for preparing an ultra-thick silver-containing chromium nitride coating according to claim 2, characterized in that: The substrate is an iron-based alloy.

6. The method for preparing an ultra-thick silver-containing chromium nitride coating according to claim 5, characterized in that: The iron-based alloy is subjected to surface strengthening treatment, and the surface strengthening treatment method is nitriding or pre-plating with a chromium coating.